What has Happened to MSMEs Performance during the Pandemic in Central Java, Indonesia? - Violinda, Qristin; sumastuti, Efriyani; Ayoup, Hazeline (KnE Social Sciences, 2022)
This study aims to determine the relationship between survival strategies, legal protection, and demographic factors (business tenure, age, education level, marital status, and types of capital) with the performance of MSMEs in Central Java. The sampling method used was simple random sampling with a sample size of 153 MSMEs actors. The analysis used was multiple linear using SPSS 24.00. The results of this study show that the independent variable of Survival Strategy (X1) has a significant effect and contributed to forming resilience (Y1) of 75.8%. Secondly, the independent variable of legal protection (X2) has no significant effect in forming resilience (Y1); the contribution is only -2.0%, and the existence of legal protection decreases resilience by 2%. Thirdly, the relative contribution of the survival strategy (X1) independent variable in shaping resilience (Y1) is 102.7%. Fourthly, the relative contribution of the legal protection independent variable (X2) in shaping resilience (Y1) is -2.7%. Lastly, Diploma/Bachelor’s degrees have higher resilience than High School/Vocational School degrees, in which a bachelor’s degree contributes 59.32% to resilience. The study also shows that there is no resilience difference in each group of business status, age, business tenure, and types of capital. Keywords: demographic factors, legal protection, MSMEs, resilience, survival strategy